2006
DOI: 10.1007/s00268-005-7980-0
|View full text |Cite
|
Sign up to set email alerts
|

New Type of Jejunal Interposition Method after Gastrectomy

Abstract: The comparative analysis of the results of the new operation (75 patients) with 80 patients (who were operated on using the traditional method) after the Roux-en-Y operation showed the significant advantages of the new method due to a diminished occurrence of troublesome gastrointestinal symptoms. We consider that the reconstruction of the gastrointestinal tract after total gastrectomy should give the maximal comfort for the rest of the patient's life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
0
7
0
3
Order By: Relevance
“…5). The initial report of early results showed the pouch groups to have the best nutrition, particularly with Roux-en-Y Journal of Surgical Oncology DOI 10.1002/jso [35]) but two other trials (Schwarz et al [34] and Zherlov et al [38]) showed better body weight data and less symptoms with reconstruction using the duodenal passage route. The recent Zherlov study is not very convincing, however, since the control group here had no intestinal reservoir, but the Schwarz study had two pouch groups, one with Roux-en-Y and one interposed through the duodenum.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…5). The initial report of early results showed the pouch groups to have the best nutrition, particularly with Roux-en-Y Journal of Surgical Oncology DOI 10.1002/jso [35]) but two other trials (Schwarz et al [34] and Zherlov et al [38]) showed better body weight data and less symptoms with reconstruction using the duodenal passage route. The recent Zherlov study is not very convincing, however, since the control group here had no intestinal reservoir, but the Schwarz study had two pouch groups, one with Roux-en-Y and one interposed through the duodenum.…”
Section: Resultsmentioning
confidence: 97%
“…Another variation is the addition of a plication around the esophagojejunostomy for reflux correction (Yumiba et al [43]). Zherlov et al [38] suggested a valvelike procedure at the esophagojejunal anastomosis for a similar purpose and Florio et al [48] described enlargement of reservoir capacity by a modification of the jejunal pouch with distal Roux-en-Y, that of increasing pouch capacity by making the Roux-en-Y anastomosis unusually long. However, limited or lack of any meaningful outcome data make a meaningful assessment of these variations in operative technique impossible.…”
Section: Discussionmentioning
confidence: 97%
“…However, no reconstruction procedures have been reported to meet all the above requirements. 2,[4][5][6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches of open surgeries including Roux en Y (gastrojejunostomy), Billroth I and jejunal loop interposition (jejunoduodenostomy) and Billroth II (gastrojejunal anastomosis) were used to reconstruct partial or total gastrectomy [1-4]. Comparing Roux en Y and Billroth II procedures, the Roux-en-Y approach showed less reflux symptoms and less chronic fundic atrophic gastritis [5].…”
Section: Introductionmentioning
confidence: 99%